Analisis Dan Usulan Perencanaan Tata Letak Pabrik Bagian Produksi Menggunakan Metode Systematic Layout Planning (SLP) Di PT.ABC - Muhammad Fajar Hafidin; Asep Erik Nugraha (Fakultas Teknik Universitas Tulang Bawang, 2023)
Good factory layout planning is one of the factors that can increase company productivity. Layout is a facility design, layout analysis, concept formation, as well as the embodiment of the system for making goods or services. Applying a good layout in a company can cut the time needed in a production process and also reduce the energy that must be expended by workers. This research was conducted at PT. ABC is part of the Drivetrain Unit Department located in the Bukit Indah City Industrial Area, Purwakarta, West Java. The object to be observed is the layout of the factory for the production of single part trunnion which is devoted to the seat trunnion sub-component. The research method used is quantitative method. Data processing used to solve problems at PT. ABC uses the Systematic Layout Planning (SLP) Method approach. The goal is to be able to optimize the existing layout and increase the efficiency and effectiveness of the productivity of the company's performance. The conclusion is that the current condition of the factory layout is quite effective because it can produce one trunnion product faster than the predetermined takt time. However, there are still some improvements in the layout of the factory and the production process. Researchers try to provide suggestions for the layout of the new factory and its production process. The result is that the suggested layout has a time that is 94 seconds faster than before. Keywords: Layout, Production, Productivity, Systematic Layout Planning